KEY DRIVERS OF BRAND LOYALTY AMONG MALAYSIAN SHOPPERS: EVIDENCE FROM A JAPANESE FASHION RETAILER - Jasmine A.L. Yeap; T. Ramayah; Emily H.T. Yapp (Asian Academy of Management Journal, 2018)
Due to the uncertain, changing landscape and challenges in the fast-moving fashion retailing market, fashion retailers have to find their way to stay competitive and survive in the market. One of the ways is through effective use of branding. Focusing on a currentlyleading, Japanese fast fashion retailer (Uniqlo), this research sought to determine the branding attributes which could lead to the formation of brand loyalty among customers. The Service Brand Verdict Model (SBVM) served as the basis for this study’s research model. Through the partial least squares (SmartPLS 3.2.6) analysis on 309 Uniqlo customers, the results showed that merchandise, value-for-money, feelings, self-image congruence and uncontrolled communications are significant aspects that contribute to building brand loyalty among customers. In building intense and active loyalty among customers, both tangible and rational aspects of a brand as well as the imagery and emotional aspects of it need to be integrated in strategic branding decisions.